3D printing fabrication of porous bismuth antimony telluride and study of the thermoelectric properties. (January 2019) - Shi, Jianxu; Chen, Hualing; Jia, Shuhai; Wang, Wanjun
Graphical abstract: Highlights: P-type Bi0.5Sb1.5Te3 (BST) was fabricated using additive manufacturing method. The selective-laser-sintering (SLS) helps to produce porous thermoelectric (TE) material. It simplifies the process of TE materials compared with traditional technique. Higher ZT value than the bulk material was obtained. Abstract: This paper reports the successful preparation of porous thermoelectric samples of bismuth antimony telluride (Bi0.5 Sb1.5 Te3, BST) using 3D printing technology. The porous thermoelectric samples were fabricated with selective laser sintering (SLS) method using 100 mesh BST powders. Their thermoelectric performances, including electrical conductivity, Seebeck coefficient, and thermal conductivity in the temperature range of 25℃ - 250℃ were measured. The electrical conductivity was found to have a maximum value 4.03 × 10 4 S/m, lower than maximum value 7.36 × 10 4 S/m of the bulk BST. The Seebeck coefficient of the porous samples was found have a maximum value at 190.51 μV/K, slightly higher than that of the BST bulk alloy. The minimum thermal conductivity of the porous BST samples was measured to be 0.27 W/mK at 54℃, less than 18% of minimum that for the bulk BST alloy. The thermal conductivity is reduced due to boundaries and defects formed in SLS process as well as the porous structures of the samples. The figure of merit (ZT) of the porous samples was found to have a maximum value of about 1.29, higher than that of the BST bulk material.